PERLINDUNGAN HUKUM KONSUMEN TERHADAP PRAKTIK TEKNOLOGI FINANSIAL ILEGAL DALAM BENTUK PINJAMAN ONLINE ILEGAL - Poernomo, Sri Lestari (Mimbar Keadilan, 2022)
Along with the times and the rapid advancement of technology and information, it has led to the emergence of financial services using information technology. This progress can encourage developments in life to modernizing society. This certainly has a positive impact such as helping and making it easier to complete work for financial technology (fintech) business actors. However, it still has a negative impact in the form of crime by using electronic media as a crime tool. Crimes that are increasingly prevalent in society are fraud through electronic media and information such as online loan fraud, which causes a lot of harm to the community. This illegal online loan is an illustration of the simplification of the financing system which is facilitated by attractive offers without complicated bureaucracy, which turned out to be a time bomb for the community because it ensnared various complex problems in it. This research is normative research using an approach based on laws. The lack of legal protection for online fund borrowers has resulted in various legal phenomena that arise and become friction within the community, inadequate regulations have resulted in many business actors in the field of financial technology arbitrarily carrying out their business practices without considering the safety and legal protection of users of loan services online. The number of start-up business actors who run the online loan business and do not pay attention to licensing or illegal activities has the potential to cause problems because they are not subject to existing regulations, the absence of supervision and guidance for financial technology business actors causes a lack of control of business traffic in the financial technology sector. this financial technology.